Abu’l–‘Izz al-Jazari and His Role in The Advancement of the Science of Mechanics (1136-1206) - Ali, Nariman Abdalla; Tofiq, Jihad Nuri (JURNAL JAWI, 2022)
Abu’l-‘Izz al-Jazari is considered one of the pioneers of mechanical engineering in the middle Islamic centuries. He is known not only as a collector of previous scientists' thoughts but also as an inventor and a mechanical engineering designer.Writing about this scientist is of special significance because it basically explains an important and neglected aspect of mechanical science. This study aims to shed light on al-Jazari’s efforts in the field of mechanics based on the documents and resources of Islamic history as well as foreign resources.